2014
DOI: 10.4097/kjae.2014.66.3.230
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor, family C, group 5 (GPRC5B) downregulation in spinal cord neurons is involved in neuropathic pain

Abstract: BackgroundG protein-coupled receptor, family C, group 5 (GPRC5B), a retinoic acid-inducible orphan G-protein-coupled receptor (GPCR), is a member of the group C metabotropic glutamate receptor family proteins presumably related in non-canonical Wnt signaling. In this study, we investigated altered GPRC5B expression in the dorsal horn of the spinal cord after spinal nerve injury and its involvement in the development of neuropathic pain.MethodsAfter induction of anesthesia by intraperitoneal injection of pentob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…These results suggest that Cd may strengthen its toxicity via the suppression of GPRC5B gene expression in HK-2 cells. Several studies demonstrated that GPRC5B might be involved in neuropathic pain and insulin secretion (Soni et al, 2013;Chung et al, 2014). However, the role of GPRC5B in kidney function or Cd-induced renal toxicity has not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that Cd may strengthen its toxicity via the suppression of GPRC5B gene expression in HK-2 cells. Several studies demonstrated that GPRC5B might be involved in neuropathic pain and insulin secretion (Soni et al, 2013;Chung et al, 2014). However, the role of GPRC5B in kidney function or Cd-induced renal toxicity has not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…G protein-coupled receptor, family C, group 5 (GPRC5B) have been shown to be related in non-canonical WNT signaling. Down-regulation of GPRC5B in the dorsal horn of the spinal cord neurons is correlated with an increased NP following a SCI [30] . Not only have GPCRs, such as GPRC5B, been shown as an evidence of NP in the SCI, but GCPRs have also been detected in the paraventricular nucleus and supraoptic nucleus of the hypothalamus [31] .…”
Section: Functions Of the Hypothalamus And Implications Of Npmentioning
confidence: 97%
“…Some chronic pain conditions such as rheumatoid arthritis and fibromyalgia have been directly linked to abnormalities in the hypothalamo-pituitaryadrenal axis (HPA); however, the role of HPA axis on NP is currently unknown [29] . Gene-protein coupled receptors (GPCRs) are the major targets for hormones, neurotransmitters, neuropeptides in the nervous system, and are important for drug development targeting NP [30] . G protein-coupled receptor, family C, group 5 (GPRC5B) have been shown to be related in non-canonical WNT signaling.…”
Section: Functions Of the Hypothalamus And Implications Of Npmentioning
confidence: 99%
“…GPR5B codes for a G protein-coupled receptor, which is a member of the group C metabotropic glutamate receptor family. This protein is required for neuronal fate determination in the brain [ 45 ] and GPR5B downregulation affects microglial activation [ 75 ]. Directly linked to GPR5B ( Figure 3 ) appears PCOLCE2 , a gene coding for a procollagen C-proteinase enhancer [ 54 ] and involved in the regulation of proapolipoprotein (apo) AI (apoAI) posttranslational processing [ 55 ]: apoAI binds β -amyloid peptide, a major protein in the brain associated with Alzheimer's and Parkinson's diseases, thus preventing Abeta-induced neurotoxicity [ 76 ].…”
Section: Lc Networkmentioning
confidence: 99%